KONJUNGSI KORELATIF DALAM BERITA UTAMA SURAT KABAR TRIBUN PEKANBARU - Mintari J. E. Sirait; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determined the percentage of accurate use of correltive conjunction in Pekanbaru Tribun newspaper and the cause of inaccurate use of correlative conjunction in Pekanbaru Tribun newspaper. The method used in this study was descriptive method with qualitative apporoach. The data source in this study was Pekanbaru Tribun newspaper edition 1 until March 31, 2017. The data of this study was all sentence that use correlative conjunction in Pekanbaru Tribun newspaper. The result finding of this study seen from the use of conjunction in headline of Pekanbaru Tribun newspaper for one month. Based on the results of this study found that 73,17% of appropriate use and 26,83% are not appropriate.Keyword: conjunction use, corelative conjunction, headline, tribun pekanbaru.